A choroid plexus epithelial cell-based model of the human blood-cerebrospinal fluid barrier to study bacterial infection from the basolateral side - Dinner, Stefanie; Borkowski, Julia; Stump-Guthier, Carolin; Tenenbaum, Tobias; Schroten, Horst; Schwerk, Christian (JoVE. Video journal, 2016)
The epithelial cells of the choroid plexus (CP), located in the ventricular system of the brain, form the blood-cerebrospinal fluid barrier (BCSFB). The BCSFB functions in separating the cerebrospinal fluid (CSF) from the blood and restricting the molecular exchange to a minimum extent. An in vitro model of the BCSFB is based on cells derived from a human choroid plexus papilloma (HIBCPP). HIBCPP cells display typical barrier functions including formation of tight junctions (TJs), development of a transepithelial electrical resistance (TEER), as well as minor permeabilities for macromolecules. There are several pathogens that can enter the central nervous system (CNS) via the BCSFB and subsequently cause severe disease like meningitis. One of these pathogens is Neisseria meningitidis (N. meningitidis), a human-specific bacterium. Employing the HIBCPP cells in an inverted cell culture filter insert system enables to study interactions of pathogens with cells of the BCSFB from the basolateral cell side, which is relevant in vivo. In this article, we describe seeding and culturing of HIBCPP cells on cell culture inserts. Further, infection of the cells with N. meningitidis along with analysis of invaded and adhered bacteria via double immunofluorescence is demonstrated. As the cells of the CP are also involved in other diseases, including neurodegenerative disorders like Alzheimer`s disease and Multiple Sclerosis, as well as during the brain metastasis of tumor cells, the model system can also be applied in other fields of research. It provides the potential to decipher molecular mechanisms and to identify novel therapeutic targets.